2020
DOI: 10.1042/cs20201224
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome dysbiosis alleviates the progression of osteoarthritis in mice

Abstract: Gut microbiota dysbiosis has been studied under the pathological conditions of osteoarthritis (OA). However, the effect of antibiotic-induced gut flora dysbiosis on OA remains incompletely understood at present. Herein, we used a mouse (8 weeks) OA model of destabilization of the medial meniscus (DMM) and gut microbiome dysbiosis induced by antibiotic treatment with ampicillin and neomycin for 8 weeks. The results show that antibiotic-induced intestinal microbiota dysbiosis reduced the serum level of lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 69 publications
1
44
0
2
Order By: Relevance
“…Furthermore, antibiotic treatment prior to injury has been shown to mitigate OA caused by a loading-induced injury 25 , as well as in toll-like receptor 5 knockout mice that are protected from metabolic syndrome 26 . Antibiotic-induced dysbiosis from treatment with ampicillin and neomycin reduced serum levels of LPS and improved OA outcomes after injury 27 , further illustrating that ablation of certain microbes could be a viable preventative treatment strategy for cartilage damage. Associations between the gut microbiome, muscle quality 28 , and bone strength 29 , contributors to OA pathogenesis 30 , have also been identified, suggesting that modulating the microbiome could have broad protective applications on the joint organ system.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, antibiotic treatment prior to injury has been shown to mitigate OA caused by a loading-induced injury 25 , as well as in toll-like receptor 5 knockout mice that are protected from metabolic syndrome 26 . Antibiotic-induced dysbiosis from treatment with ampicillin and neomycin reduced serum levels of LPS and improved OA outcomes after injury 27 , further illustrating that ablation of certain microbes could be a viable preventative treatment strategy for cartilage damage. Associations between the gut microbiome, muscle quality 28 , and bone strength 29 , contributors to OA pathogenesis 30 , have also been identified, suggesting that modulating the microbiome could have broad protective applications on the joint organ system.…”
Section: Discussionmentioning
confidence: 96%
“…prevalence are probably able to dysregulate the delicate balance of pro-inflammatory markers [ 34 ]. However, two of the studies we included in our analysis [ 36 , 37 ], reported that gut microbiome dysbiosis alleviates the progression of osteoarthritis in mice. Additionally, an antibiotic-induced gut microbiota dysbiosis in OA male mice significantly decreased the relative abundance of Bacteroidetes, but for female mice, the relative abundance of Firmicutes was increased significantly compared with that in Con-OA female mice [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, two of the studies we included in our analysis [ 36 , 37 ], reported that gut microbiome dysbiosis alleviates the progression of osteoarthritis in mice. Additionally, an antibiotic-induced gut microbiota dysbiosis in OA male mice significantly decreased the relative abundance of Bacteroidetes, but for female mice, the relative abundance of Firmicutes was increased significantly compared with that in Con-OA female mice [ 37 ]. While this further highlights the pivotal role of the microbiota as whole in the development, progression and symptomatology of OA, also induces contradictory conclusion about bacterial diversity and F/B ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of fecal materials from metabolic syndrome patients in GF mice enhanced gut permeability by downregulating TJ proteins ZO-1 and occludin, causing elevated plasma level of LPS and subsequently exacerbated OA severity ( Huang et al., 2020 ). Antibiotic treatment altered gut microbiota and decreased serum LPS level, alleviating circulating inflammation and preventing OA progression ( Guan et al., 2020 ). Estrogen-deficient mice exhibited pathological bone loss and impaired bone microarchitecture in femur, with downregulated gut epithelial TJ protein expression and increased serum endotoxin levels, and these pathologies could be prevented by probiotics administration ( Li J. Y. et al., 2016 ).…”
Section: Underlying Mechanisms Of Gut-alveolar Bone Axismentioning
confidence: 99%